Spondyloocular Syndrome: Novel Mutations in XYLT2 Gene and Expansion of the Phenotypic Spectrum. (4th April 2016) - Taylan, Fulya; Costantini, Alice; Coles, Nicole; Pekkinen, Minna; Héon, Elise; Şıklar, Zeynep; Berberoğlu, Merih; Kämpe, Anders; Kıykım, Ertuğrul; Grigelioniene, Giedre; Tüysüz, Beyhan; Mäkitie, Outi
ABSTRACT: Spondyloocular syndrome is an autosomal‐recessive disorder with spinal compression fractures, osteoporosis, and cataract. Mutations in XYLT2, encoding isoform of xylosyltransferase, were recently identified as the cause of the syndrome. We report on 4 patients, 2 unrelated patients and 2 siblings, with spondyloocular syndrome and novel mutations in XYLT2 . Exome sequencing revealed a homozygous nonsense mutation, NM_022167.3(XYLT2): c.2188C>T, resulting in a premature stop codon (p.Arg730*) in a female patient. The patient presents visual impairment, generalized osteoporosis, short stature with short trunk, spinal compression fractures, and increased intervertebral disc space and hearing loss. We extended our XYLT2 analysis to a cohort of 22 patients with generalized osteoporosis, mostly from consanguineous families. In this cohort, we found by Sanger sequencing 2 siblings and 1 single patient who were homozygous for missense mutations in the XYLT2 gene (p.Arg563Gly and p.Leu605Pro). The patients had osteoporosis, compression fractures, cataracts, and hearing loss. Bisphosphonate treatment in 1 patient resulted in almost complete normalization of vertebral structures by adolescence, whereas treatment response in the others was variable. This report together with a previous study shows that mutations in the XYLT2 gene result in a variable phenotype dominated by spinal osteoporosis, cataract, and hearing loss. © 2016 American Society for Bone and Mineral Research.